Hukum Waris Dan Pembagian Waris Di Indonesia - Muhammad Al Mansur; Shally Fiqih Alvani; Nova Arianti (Al Fuadiy Jurnal Hukum Keluarga Islam, 2023)
Islamic Sharia establishes inheritance rules in a very regular and fair form. It stipulates the right to property ownership for every human being, both men and women, in a legal manner. Islamic Sharia also stipulates the right to transfer ownership of a person after death to his heirs from all his relatives and lineages. Islam details and explains through the Qur'an al-Karim the share of each heir with the aim of realizing justice in society. Inheritance according to Civil Law is inheritance law in the form of a set of legal provisions that regulate legal consequences. Traditional inheritance law is actually the law of passing on wealth from one generation to its descendants.